Teaching Chinese Language in the International School Context - Hong, Jia-Fei.; SI, Chung-Mou. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book explores the learning and teaching of K-12 Chinese language in international schools. The authors of this book are scholars from teaching training institutions and universities, as well as professional frontline teachers. With a combination of the works and insights from both perspectives of theory and practice, the book presents how theories of teaching can be operated in classroom to improve the effectiveness of language teaching. It covers curriculum setting, design of teaching materials, teaching principles, methods, strategies, and evaluation. The book also discusses issues and concepts such as concept-driven learning, identity change and recognition of L1 and L2 Chinese teacher, pinyin teaching, Chinese character teaching, evaluation for learning improvement, and integration of South Asian non-Chinese speaking students into local schools. It emphasizes empirical action research methods. This is a highly informative and carefully presented book, providing high value insights to scholars from university and teacher training institutions and teachers from kindergartens, primary, and secondary schools around the world.
1 -- From Theory to Practice: Applying Didactics and Inquiry Method in IBDP Chinese A Curriculum Hsiao, Shih-Hsuan -- 2 -- Measuring Chinese Reading Comprehension Online with SmartReading Diagnostic Assessment of Chinese Competence in International School Learners Hong, Jia-Fei, Sung, Yao-Tin -- 3 -- Developing Assessment of Concept-Based Learning in Chinese as a Foreign Language: An Initial Exploration Lam, Sin Manw Sophia, Mak, Chun-Man, Lam, Daniel -- 4 -- Pedagogical Issues of Collaborative Teaching in "Learning Communities": An Exploratory Study of Co-Teaching Chinese Lam Tung-Fei, Lau Kwok-Ling -- 5 -- Integrated Performance Assessment (IPA): AP® Chinese Exam Liu May -- 6 -- Exploring L1-L2 Identity Transition in Chinese Language Teachers in Hong Kong International Schools Li, Zhen, Si, Chung-Mou -- 7 -- Use of Effective Formative Assessment Tools to Enhance Chinese Language Learning in International School Settings Li, Joanne -- 8 -- Dynamic Enrichment Learning Mode: A New Way to Facilitate the Learning of Chinese as a Second Language in the Mainstream Curriculum Loh, Ka Yee Elizabeth, Chan, Sing Pui Tikky, Fung, Wai Yan Renee -- 9 -- The acceptance and attitude of pre-service teacher to online TCSL teacher training courses for international schools Tsai, Ya-Hsun -- 10 -- Learning Strategies for Writing Chinese Characters by CSL Students in International Schools Ye, Lijing, Liang, Yuan -- 11 -- Chinese Pinyin Teaching at International Schools (Primary Section) in Hong Kong Zhang, Ling, Wu, Zhe.
Keywords: Language and languages -- Study and teaching; Asia -- Languages; Language Education; Language Teaching and Learning; Asian Languages